Assessment Of Access To Sanitation For Communities In Tapin Regency, South Kalimantan Province - Chaniago, Rian Yaitsar; Supraba, Intan; Firdiansyah, Agus (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2025)
Providing access to sanitation is one of the global and national commitments in order to improve people's welfare. Inadequate sanitation results in a number of health risks such as diarrhea, malnutrition, stunted growth, and several other health problems. The purpose of this study was to identify the accessibility of proper sanitation for the people of Tapin Regency. The scope of this study was the condition of sanitation facilities and infrastructure available in homes in Tapin District. The methods used in this research were interviews, field observations, and documentation. Data sources were determined using purposive sampling techniques. Based on the findings in the field, some people still practice open defecation even though they have a toilet at home. A more economically viable alternative for the community for a sustainable sanitation system is to concentrate on safe fecal disposal for those using latrines rather than building a new large-scale wastewater system. There are 5 indicators studied to determine the level of access to community sanitation, namely the availability of handwashing with soap and clean water facilities, access to proper sanitation, open defecation behavior, access to household wastewater management systems, and access to septage management systems. This study highlights the importance of using comprehensive sanitation indicators beyond basic latrine access, especially in rural areas where data is limited, local governments should prioritize investment in fecal sludge treatment infrastructure and strengthen community engagement in sanitation behavior change programs.